PENGEMBANGAN MEDIA PARU-PARU BUATAN BERBASIS MANEKIN PADA MATERI SISTEM PERNAPASAN MANUSIA - Lukman Nulhakim; Encep Andriana; Dhika Anggi Sandika (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports the development of a mannequin-based artificial lung learning media to find out how fifth-grade students respond at SDN Merak II to use the media. The research indicates the assessment results from media experts obtain an average percentage score of 91.10% in the